Neuro-otological abnormalities in Friedreich's ataxia. Issue 1 (January 1984) - Ell, J; Prasher, D; Rudge, P
Abstract : Ten patients with an accepted diagnosis of Friedreich's ataxia have been examined neuro-otologically, and oculomotor, vestibular and auditory function assessed. Brainstem auditory evoked potentials (BAEPs) were also recorded. A high incidence of various eye movement disorders was noted. Some of these were indicative of cerebellar dysfunction. Reduced vestibular function and impaired hearing were common to most of the patients. BAEPs were also abnormal in the majority; reasons underlying these abnormalities are discussed. Neuro-otologically, the patients did not constitute an homogeneous group. The findings cast doubt upon the accuracy and validity of the currently accepted criteria for the diagnosis and classification of the spinocerebellar degenerations.